Sire Distribution of Calves in a Beef Herd with Use of Fixed Time Artificial Insemination Followed by Immediate Bull Exposure for Natural Service in Cows and Heifers - A. R. Hartman; E. D. McCabe; D. R. Jacobs; K. E. Fike; D. M. Grieger (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:Our objective was to determine the relative percentages of calves sired by either natural service sire or fixed time artificial insemination (FTAI) sire within the same estrous period. Study Description:During two consecutive years, heifers and cows were synchronized and inseminated using the 7-day CO-Synch + CIDR FTAI protocol. All females were exposed to natural service bulls immediately following insemination. After calving, DNA was collected from a random subset of calves born in the first 21 days of the calving season for parentage analysis. Calves born from heifers totaled 59 in Year 1 and 82 in Year 2; calves born from cows totaled 89 in Year 1 and 102 in Year 2. Results:In Year 1, among calves born from heifers, the percentage sired by natural service was 5.1% (n = 3/59). Among calves born from cows, the percentage sired by natural service was 14.6% (n = 13/89). In Year 2, among calves born from heifers, the percentage sired by natural service was 9.8% (n = 8/82). Among calves born from cows, the percentage sired by natural service was 20.6% (n = 21/102). The Bottom Line:If commercial producers use FTAI followed by immediate bull exposure in beef females, it can be expected that natural service bulls may sire 5 to 20% of calves born early in the calving season while reducing time and labor associated with bull turnout.
Keywords: parentage; estrus synchronization; cow-calf